Are trees alive? - Miller, Debbie S.; Schuett, Stacey (New York : Walker, 2002)
An introduction to trees that compares parts of a tree to parts of the human body, with illustrations and brief descriptions of trees found around the world.
Maps on lining papers.
G4
Keywords: Trees -- Juvenile literature; Trees -- Ecology -- Juvenile literature; Forest ecology -- Juvenile literature; Forest animals -- Juvenile literature; Trees; Trees -- Ecology; Forest ecology; Forest animals; Ecology